Comparison of 30‐day mortality and myocardial scar indices for patients treated with prehospital reduced dose fibrinolytic followed by percutaneous coronary intervention versus percutaneous coronary intervention alone for treatment of ST‐elevation myocardial infarction. Issue 5 (29th March 2016) - Solhpour, Amirreza; Chang, Kay‐Won; Arain, Salman A.; Balan, Prakash; Zhao, Yelin; Loghin, Catalin; McCarthy, James J.; Vernon Anderson, H.; Smalling, Richard W.
Abstract : Objectives: We investigated whether prehospital, reduced dose fibrinolysis coupled with urgent percutaneous coronary intervention (FAST‐PCI) reduces mortality and cardiac magnetic resonance (CMR) measures of infarct size, compared with primary percutaneous coronary intervention (PPCI), in patients with ST‐elevation myocardial infarction (STEMI). Background: Current standard therapy for STEMI is PPCI. However, FAST‐PCI may shorten ischemic time (IT) and improve outcomes. Methods: Eligible STEMI patients received prehospital, reduced dose fibrinolysis along with standard therapy, and were transported for urgent percutaneous coronary intervention, or else they received usual treatment without prehospital fibrinolysis. Patients were divided retrospectively into four groups based on IT (<120, 120–179, 180–239 min, ≥240) for a mortality analysis cohort, and into three groups (<120, 120–179, ≥180 min) for a CMR analysis cohort. Within each IT group, patients were compared by FAST‐PCI vs. PPCI strategy. Results: Between 1/2007 and 2/2014, 1, 112 STEMI patients were treated. FAST‐PCI was employed in 551 and PPCI in 561. Of these, 357 (32.1%) underwent CMR. The treatment groups were well matched. In STEMI patients with short IT (<120 and 120–179 min groups), those treated by FAST‐PCI had lower 30‐day mortality and myocardial scar sizes compared with PPCI treatment. For IT ≥180 min, the mortalities and myocardial scar sizes were equivalent for both groups. Conclusions: In STEMI patients with IT <180 min, FAST‐PCI may reduce 30‐day mortality and myocardial scar size compared with PPCI. This suggests that infarct interventions must be instituted within 3 hr of symptom onset in order to detect an optimal beneficial effect both clinically and by CMR measurement. © 2016 Wiley Periodicals, Inc.